Pemetaan Tingkat Kebisingan Di PKS Terantam PT. Perkebunan Nusantara V Dengan Metode Noise Mapping - Urip Rifani; Aryo Sasmita; Edward Edward (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
PT. Perkebunan Nusantara V in its operational activities has the potential to generate noise coming from palm oil production machines. Workers who are constantly exposed to noise have the potential to affect workers' health and comfort. The purpose of this research is to know the intensity of noise generated by oil palm production machine, exposure time, map of noise distribution pattern, and noise control effort. The noise measurement method refers to the noise mapping method and the tool used is the Sound Level Meter (SLM). Measurement based on the noise mapping method is done for 1 day. The results showed that from 92 points of measurement, there were 71 points showing numbers that exceeded the quality standard. The highest noise level is 100.6 dB where it is very close to the noisy source, and the lowest noise level is 81.7 Db which is far enough from the noisy source. Based on the calculation using NIOSH formula from 92 point of noise mapping method, there are 61 dots showing exposure time above NIOSH recommended standard. The highest noise level was 100.6 dB with a duration of 13.1 minutes and the lowest noise level was 81.7 dB with a duration of 1028.9 minutes. Sound mapping using the Surfer 11 program to find out the pattern of noise distribution caused by the noise mapping method. Based on the results of Surfer 11 shown by different colors of red, orange, yellow, green, blue and purple. The planned noise control measures are by engineering control, adminstrative control, and control on the recipient or worker.Keywords: Noise, NIOSH, Noise Mapping, Surfer 11, PKS Terantam